Developing farm models for sloping denuded forest lands : a case study of the Khao Kho land settlement, Petchabun, Thailand - Sivarajah, Ponniah; Demaine, Harvey; Dias, Hiran D.; Setty, E. Desingu; DAAD (German Academic Exchange) (Bangkok : Asian Institute of Technology, 1991)
The study analyses the farming systems in t he Khao Kho settlement, an area of steeply sloping land in the North of Thailand, and attempts to suggest cropping systems which are profitable and can help in the long term sustainability of farm production in the area. A randomly selected sample of 14 villages in t he area was studied and analysed . It was found, based on t he type of crops cultivated and market values, t hat three types of farming systems exists in the area viz. Low-value Cash Cropping system, Medium-value Cash Cropping system and High-value Cash Cropping system . They differed from each other socio-economic, agronomic and land type characteristics . It was also evident that crop yields varied significantly among villages. As the terrain in the area consists of steeply sloping lands, erosion problems were severe and low soil fertility levels had led declining yields for maize and ginger crops which were low input enterprises. Farm input use for different crops a nd Gross Margi n analysis is out lined in detail. Vegetables were found to be more profitable in the area, followed by mulberry. The need for provision of extension services on new crops and a market place were identified. It was also identified that labour availability in the family limits the extent of land cultivated and and t hat farm incomes were affected by t he availability of credit, land quality, extent a nd size of family labour force. Using the crop gross margin analysis and labour requirements for different crops , mod e l farm plans are formulated taking , into consideration family labour availability (family size) and land quality constraints, which would give high returns for t he settlers in the new villages to be established. Finally, recommendation s for planning to improve the living standards of the settlers by assisting them to adopt appropriate farming systems , and for further research are given.
A thesis submitted in partial fulfillment of the requirements for the award of the Degree of Master of Science
Thesis (M.Sc.) - Asian Institute of Technology, 1991
Keywords: Land settlement -- Thailand -- Khao Kho